2016
DOI: 10.5005/jp-journals-10024-1869
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gingival Health Status among 6- and 12-years-old Children in Dhamar City, Yemen: A Cross-sectional Study

Abstract: Introduction: Epidemiological data on gingivitis in children are important for understanding the natural course of the disease, identifying its risk factors, and predicting its time trends. The objective of this study was to evaluate the prevalence and severity of gingivitis among 6-and 12-year-old school children in Dhamar city, Yemen. Materials and methods:A total of 663 children (310 children of 6 years old and 353 children of 12 years old) were examined from 10 public primary schools. Gingival health statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
1
9
1
1
Order By: Relevance
“…In the present study, the mean PI was (1.39) which is greater than those PI means shown by other researchers in other populations like in: Damascus (1.12) (in 1996 by Dashash, age group 6–12 years) [12], Jordan (0.61) [13], Sanaa city in Yemen (1.25) [14], Dhamar city in Yemen (1.37) [15], and the Khartoum state in the Sudan (1.30) [16]. In the present study, the mean GI was (1.12) which is greater than other GI means shown by other researchers in different literature of other populations like in: Jordan (0.77) [13], Dhamar city in Yemen (0.98) [15], and the Khartoum state in the Sudan (1.05) [16]. Also, the GI mean reached in our study is smaller than the results shown by other researchers in other populations like in: Damascus (1.51) (again in 1996 by Dashash, age group 6–12 years) [12], Sanaa city in Yemen (1.36) [14], and Mayanamar (1.22) [17].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In the present study, the mean PI was (1.39) which is greater than those PI means shown by other researchers in other populations like in: Damascus (1.12) (in 1996 by Dashash, age group 6–12 years) [12], Jordan (0.61) [13], Sanaa city in Yemen (1.25) [14], Dhamar city in Yemen (1.37) [15], and the Khartoum state in the Sudan (1.30) [16]. In the present study, the mean GI was (1.12) which is greater than other GI means shown by other researchers in different literature of other populations like in: Jordan (0.77) [13], Dhamar city in Yemen (0.98) [15], and the Khartoum state in the Sudan (1.05) [16]. Also, the GI mean reached in our study is smaller than the results shown by other researchers in other populations like in: Damascus (1.51) (again in 1996 by Dashash, age group 6–12 years) [12], Sanaa city in Yemen (1.36) [14], and Mayanamar (1.22) [17].…”
Section: Discussioncontrasting
confidence: 68%
“…Also, the GI mean reached in our study is smaller than the results shown by other researchers in other populations like in: Damascus (1.51) (again in 1996 by Dashash, age group 6–12 years) [12], Sanaa city in Yemen (1.36) [14], and Mayanamar (1.22) [17]. Also, gingivitis prevalence rate was as high as (97.93%) which is higher than other gingivitis prevalence rates shown in different populations like in: Damascus (90.0%) (again in 1996 by Dashash, age group 6–12 years) [12], Jordan (70.2%) (mild 38.5%, moderate 31.4%, severe 0.3%) [13], Dhamar city in Yemen (86.4%) (mild 59.3%, moderate 25.8%, severe 1.4%) [15], Puerto Rico (80.41%) [18]. Still, the gingivitis prevalence rate reached in this present study was less than that reached in Sanaa city in Yemen in which all the study sample had gingivitis [14].…”
Section: Discussionmentioning
confidence: 99%
“…For periodontal diseases, most literature suggests that male teenagers are more likely to develop gingivitis and have suboptimal oral hygiene [18][19][20][21] . However, some studies report the absence of significant gender inequalities in the periodontal status of children [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies show a higher prevalence of gingivitis in adolescents aged 12 and 13 years, compared with children between 5 and 11 years of age (19,20). This is favored by various factors, including an increase in the levels of steroid hormones and cellular receptors of these hormones in gingival tissue cells, which favors gingival inflammation during puberty (21).…”
Section: Introductionmentioning
confidence: 99%